Effect of cooling rates on shape and crystal size distributions of mefenamic acid polymorph in ethyl acetate - Abdul Mudalip, S. K.; Adam, Fatmawati; Jamal, Parveen; Abu Bakar, Mohd Rushdi; Amran, Nur Amelia; Sulaiman, Siti Zubaidah; Che Man, Rohaida; Mohd Arshad, Z.I.; Shaarani, Shalyda Md (IOP Publishing, 2017)
This study investigate the effect of cooling rates on mefenamic acid crystallisation in ethyl acetate. The cooling rate was varied from 0.2 to 5 °C/min. The in-line conductivity system and turbidity system were employed to detect the onset of the crystallization process. The crystals produced were analysed using optical microscopy and Fourier transform infrared spectroscopy (FTIR). It was found that the crystals produced at different cooling rates were needle-like and exhibit polymorphic form type I. However, the aspect ratio and crystal size distributions were varied with the increased of cooling rate. A high crystals aspect ratio and narrower CSD (100−900 μm) was obtained at cooling rate of 0.5 °C/min. Thus, can be suggested as the most suitable cooling rate for crystallization of mefenamic acid in ethyl acetate.